The apartheid divestment movement at George Washington University: the legacy of student activism and GW Voices for a Free South Africa. Issue 1 (2nd January 2021) - Novak, Andrew
ABSTRACT: The antiapartheid protests at George Washington University were the campus's largest student protests since the Vietnam War. As at other universities, students advocated divestment of university finances in businesses with operations in South Africa, including through the now-iconic "shantytown" protests, which symbolized South African living conditions on campus. Under pressure from a student group, GW Voices for a Free South Africa, university leadership under President Lloyd Elliott seriously considered moving the University's stock portfolio to a South Africa-free fund but ultimately decided such a fund was too risky. Unlike other universities of its size and prestige, GW never divested. The location of the University and the size of its South African-affected stock holdings hampered divestment efforts.